Does Sick Pay Affect Workplace Absence? - Alex Bryson; Harald Dale-Olsen (Institute of Labor Economics (IZA), 2017)
Higher replacement rates often imply higher levels of absenteeism, yet even in generous welfare economies, private sick pay is provided in addition to the public sick pay. Why? Using comparative workplace data for the UK and Norway we show that the higher level of absenteeism in Norway compared to UK is related to the threshold in the Norwegian public sick pay legislation. This threshold's importance is confirmed in a Regression Kinked Design (RKD) analysis on the Norwegian micro-data. Private sick pay is provided as an employer-provided non-wage benefit and when training costs are high.
Keywords: H31; J22; J28; J32; 330; absenteeism; public sick pay; private sick pay; comparative